"Crossed homonymous hemianopia" and "crossed left hemispatial neglect" in a case of Marchiafava-Bignami disease. Issue 9 (September 1993) - Kamaki, M; Kawamura, M; Moriya, H; Hirayama, K
Abstract : "Crossed homonymous hemianopia" and "crossed left hemispatial neglect" were observed in a woman with Marchiafava-Bignami disease. Two forms of "crossed homonymous hemianopia" were observed. Initially, Goldmann perimeter testing showed a left homonymous hemianopia with the right hand and vice versa. Later, confrontation tests showed a left homonymous hemianopia, whereas visual field testing using the Goldmann perimeter (kinetic quantitative perimeter) and the OCTOPUS (Interzeag AG, static automated perimeter) showed a right homonymous hemianopia with either hand. "Crossed left hemispatial neglect" was not seen with the left hand, but neglect of the left hemifield was seen with the right hand. CT and MRI showed a lesion occupying almost the entire corpus callosum. PET showed no significant differences between comparable areas of the left and right cerebral hemispheres. These findings indicate that both signs of interhemispheric disconnection were due to the callosal lesion. Moreover, the "crossed left hemispatial neglect" can be explained as being a consequence of the dominance of the right cerebral hemisphere for visuospatial recognition.